The effect of F-75 alloy mixed with HAP on microstructure in corrosion test for biomaterial applications - Rohaya, A. M.; Shamsul Baharin, Jamaludin, Prof. Madya Dr.; Shaiful Rizam, Shamsudin (Universiti Malaysia Perlis, 2010)
International Conference on X-Rays and Related Techniques in Research and Industry (ICXRI 2010) jointly organized by Universiti Malaysia Perlis (UniMAP) and X-Ray Application Malaysia Society (XAPP), 9th - 10th June 2010 at Aseania Resort Langkawi, Malaysia.